2020
DOI: 10.2147/ndt.s232059
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Performance of the Arabic Population on the Adolescent-Adult Sensory Profile: An Observational Study</p>

Abstract: Background: The Adult-Adolescent Sensory Profile (AASP) is a questionnaire developed to measure the way in which people in different age groups respond to different sensory stimuli. These sensory stimuli may uncover different behavioral problems that may affect activities of daily living. This observational study aimed to validate the Arabic version of the AASP used to assess the sensory processing abilities of healthy individuals. Methods: Participants comprised 560 Jordanians aged 11 years and older. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the literature, it is asserted that sensory responses in healthy individuals are related to various factors such as age, gender, geographic area, culture, belief, education level and employment status. In the evaluations made according to age ranges in different cultures, and including the original AASP study, it was highlighted that reference values specific to each age group should be established (Brown and Dunn, 2002; Gándara-Gafo et al, 2019; Al-Momani et al, 2020; Almomani et al, 2014). Engel-Yeger found that a relatively high percentage of Israeli participants in the three age groups were in the performance ranges ‘more or less than most people’ in the different AASP quadrants; however, in general, quadrant mean scores and standard deviations of the evaluated population have been reported to have achieved results consistent with the AASP guideline (Engel-Yeger, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it is asserted that sensory responses in healthy individuals are related to various factors such as age, gender, geographic area, culture, belief, education level and employment status. In the evaluations made according to age ranges in different cultures, and including the original AASP study, it was highlighted that reference values specific to each age group should be established (Brown and Dunn, 2002; Gándara-Gafo et al, 2019; Al-Momani et al, 2020; Almomani et al, 2014). Engel-Yeger found that a relatively high percentage of Israeli participants in the three age groups were in the performance ranges ‘more or less than most people’ in the different AASP quadrants; however, in general, quadrant mean scores and standard deviations of the evaluated population have been reported to have achieved results consistent with the AASP guideline (Engel-Yeger, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed the cut-off scores were larger in the ‘less’ categories and higher in the ‘more than’ categories in the Arabic version. Arabic people’s different sensory stimuli responses have been associated with religion, cultural habits and the plain physical features in cities (Al-Momani et al, 2020). When the AASP Turkish sensory quadrant scores were compared to the original study reference values, Üçgül et al found that almost half of the healthy participants differed from ‘like most people’ as demonstrated in the sensory seeking (45%), sensory sensitivity (50%) and sensory avoidance (49%) quadrant scores (Üçgül et al, 2017).…”
Section: Discussionmentioning
confidence: 99%